OPTIMALISASI PEMBELAJARAN BAHASA INDONESIA MELALUI PENDEKATAN TUGAS DAN OUTPUT BAGI MAHASISWA PENDIDIKAN BAHASA INDONESIA - Halena Gena, Engel Bertha; Ida Bagus Putrayasa; I Nengah Suandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Indonesian in higher education is an important element in shaping students' communication skills, especially in the Indonesian Language Education program. To improve the effectiveness of learning, a task-based learning approach is one solution that can optimize the language learning process. This approach encourages students to actively participate through tasks that require direct application of language skills, both in speaking, writing, reading, and listening. In addition, the output produced from the task is an important indicator in assessing the success of learning. This study aims to examine how the task approach can be implemented effectively in Indonesian language learning for Indonesian Language Education students, and how the output of the task can be used to measure students' progress and language mastery. The results of this study indicate that the task approach not only increases student engagement but also strengthens practical skills in using Indonesian in academic and professional contexts. Therefore, optimizing the task-based approach and output is a very relevant strategy to create more effective, interactive, and applicable Indonesian language learning.